Critical Discourse Analysis on Venezuela's Indigenous Media: The Influence of the "New Media Nation" in Countering Negative Representation - Rebecca Angeline Davinia; Bayu Kristianto (Jurnal Impresi Indonesia, 2025)
This article examines the visual and discursive communication strategies employed by Indigenous peoples in Venezuela to counter negative representations constructed by non-Indigenous, particularly Western, media. Utilizing a qualitative approach through Critical Discourse Analysis (CDA) and visual semiotic analysis, this study focuses on two primary data sources: social media posts by President Nicolás Maduro and the Indigenous organization CONIVE (Consejo Nacional Indio de Venezuela). The research aims to explore how Indigenous communities construct counter-representations in response to colonial stereotypes such as exoticism, primitivism, passivity, and marginalization, which are frequently perpetuated by global media narratives. Framed by Hall’s theory of representation, Geertz’s concept of cultural identity, and Gramsci’s hegemony, findings show that Indigenous groups resist colonial stereotypes through media activism, cultural expression, and political advocacy. These efforts redefine Indigenous visibility and assert agency within global discourse. The study highlights the strategic role of community media in reclaiming narrative power and calls for stronger support for Indigenous communication rights.